Zinc Essentiality, Toxicity, and Its Bacterial Bioremediation: A Comprehensive Insight - Hussain, Sarfraz; Khan, Maryam; Sheikh, Taha Majid Mahmood; Mumtaz, Muhammad Zahid; Chohan, Talha Ali; Shamim, Saba; Liu, Yuhong (Frontiers in Microbiology, 2022)
Zinc is one of the most abundantly found heavy metals in the Earth’s crust, and is reported to be an essential trace metal required for the growth of living beings, with it being a co-factor of major proteins, and mediating the regulation of several immunomodulatory functions. However, its essentiality also runs parallel to its toxicity, which is induced through various anthropogenic sources, constant exposure to polluted sites and other natural phenomena. The bioavailability of zinc is attributable to various vegetables, beef, and dairy products, which are a good source of zinc for safe consumptions by humans. However, conditions of zinc toxicity can also occur through the overdosage of zinc supplements, which is increasing at an alarming rate attributing to lack of awareness. Though zinc toxicity in humans is a treatable and non-life threatening condition, several symptoms cause distress to human activities and lifestyle, including fever, breathing difficulty, nausea, chest pain, and cough. In the environment, zinc is generally found in soil and water bodies, where it is introduced through the action of weathering, and release of industrial effluents, respectively. Excessive levels of zinc in these sources can alter soil and aquatic microbial diversity, and can thus affect the bioavailability and absorption of other metals as well. Several Gram positive and negative species such as Bacillus sp., Staphylococcus sp., Streptococcus sp., and E. coli, Pseudomonas sp., Klebsiella sp., and Enterobacter sp., respectively, have been reported to be promising agents of zinc bioremediation. This review intends to present an overview of zinc and its properties, uses, bioavailability, toxicity, as well as the major mechanisms involved in its bioremediation from polluted soil and wastewaters.